Comparative Analysis of the Efficiency of the Top Ten Conventional Joint Venture Life Insurance Companies in Indonesia in the Period Before and During the Covid-19 Pandemic Using the Data Envelopment Analysis Method - Aldi Ara Ahmad; Arief Bimantoro Suharko (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to capture the efficiency level of industry players in conventional joint venture life insurance companies in Indonesia before and during the Covid-19 pandemic. Efficiency is related to the level of success of an activity being assessed in terms of the ratio between amounts of the output generated and the input used to generate the outputs in the activity. Efficiency can be measured using the Data Envelopment Analysis (DEA) method, which is a non-parametric frontier approach that uses mathematical programming with 2 (two) assumptions, namely Constant Return to Scale (CRS) and Variable Return to Scale (VRS). The variables used are input and output variables, wherein the input variables include total debt, labor costs, claims expenses, investment composition of stocks, bonds, and securities issued by the government of the Republic of Indonesia (RI). The output variables used are premium income and investment returns. The type of data used is secondary data. The data collection technique used is library research. The objects used as samples were top 10 (ten) conventional joint venture life insurance companies in terms of revenues with the data obtained from the financial reports and annual reports of each company for the period between 2015 and 2021. The analysis show that investment portfolio performances derived from the company strategy acts as the main efficiency determinant in the industry.